Mathematical models of lipoprotein metabolism and kinetics: Current status and future perspective - Lu, James; Mazer, Norm; Hübner, Katrin (Clinical lipidology, 2013)
Lipoprotein metabolism and kinetics comprises the time-dependent processes of synthesis, transformation and clearance of lipids, apolipoproteins and their assembled particles. By integrating and explaining the wealth of in vitro and clinical data available on lipoprotein metabolism and kinetics, mathematical models can provide novel insights into the underlying pathophysiology of lipid disorders, as well as quantify the effects of drugs intended for their treatment. In this article, we first discuss some basic principles of mathematical modeling in biology and drug development, and then review a number of recent publications in which different types of mathematical models have been used to investigate lipoprotein metabolism and kinetics. We conclude by posing a set of ten fundamental questions in this field that we believe mathematical modeling can potentially address, in the effort to develop novel and effective therapies for patients with high cardiovascular risk.
Gesehen am 08.06.2013